Socioeconomic Position Disparities in Cardiovascular Health Before and After the Examination of Mechanisms of Exercise-Induced Weight Compensation Randomized Controlled Trial - Candice A. Myers; Stephanie T. Broyles; Corby K. Martin (Mary Ann Liebert, 2019)
Purpose: We examined socioeconomic position (SEP) disparities in cardiovascular health before and after an exercise intervention. Methods: Data were from the Examination of Mechanisms of Exercise-Induced Weight Compensation (E-MECHANIC) study. Cardiovascular health was measured through a composite score combining body mass index, systolic blood pressure, cholesterol, and glucose. SEP was assessed using a single measure that combined income and education. Results: At baseline, there was no significant difference in cardiovascular health between high and low SEP participants. Post-intervention, this difference reached significance. Conclusion: Although cardiovascular health improved for exercise intervention participants, SEP disparities in cardiovascular health persisted during the trial.